2018
DOI: 10.1002/ijgo.12652
|View full text |Cite
|
Sign up to set email alerts
|

Colposcopic biopsy findings among women with either HPV‐16 only or HPV‐18 only who have normal cervical cytology

Abstract: Although the risk of high-grade squamous intraepithelial lesions was increased among women with HPV-16 only, this finding did not influence the rate of invasive cervical cancer when compared with women in the HPV-18 only group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Interestingly, Çöl Madendağ et al (11) reported that the detected CIN 2+ lesions with normal cytology were higher in cases of non-16/18 HPV subtypes, contrary to 16/18 HPV subtypes. Yalcin et al (12) stated that the colposcopic evaluation of the normal cytologic results of the HPV 16 cases did not increase the detection rate of cervical cancer. Conflicting results are reported in the literature in cases of negative cytology results with positive non-16/18 HPV subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Çöl Madendağ et al (11) reported that the detected CIN 2+ lesions with normal cytology were higher in cases of non-16/18 HPV subtypes, contrary to 16/18 HPV subtypes. Yalcin et al (12) stated that the colposcopic evaluation of the normal cytologic results of the HPV 16 cases did not increase the detection rate of cervical cancer. Conflicting results are reported in the literature in cases of negative cytology results with positive non-16/18 HPV subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…El diagnóstico histológico es la prueba confirmatoria para la citología cervicouterina, mientras que la colposcopia es el complemento esencial entre ambos estudios, porque permite el examen clínico y morfológico que orienta las biopsias para la histología (92).…”
Section: Histología Y Colposcopíaunclassified
“…[9][10][11][12] The initiatives to implement molecular tests in population screening are justified because there is evidence that the presence of hrHPV infection, even among women with normal cytology, increases the risk of CIN2þ and may contribute to bringing the diagnosis forward by more than a decade depending on the case. [11][12][13][14][15] In addition, HPV16/18 coinfection is related to high rates of high-grade lesions (56.7%) and cancer (71.1%), 16 which demonstrates the importance of tests based on the polymerase chain reaction (PCR) technique with genotyping of the viral types.…”
Section: Introductionmentioning
confidence: 99%